Analytical model for determining the availability of continuous surface exploitation systems, case study: I BTD system of the open pit Drmno - Gomilanović Miljan; Doderović Aleksandar; Stanić Nikola; Milijanović Aleksandar (Mining and Metallurgy Engineering Bor, 2023)
This paper presents an analytical model for determining the availability of a continuous coal system at the open pit Drmno. A continuous coal-fired system is a technical system with sequential connection of elements in terms of reliability and functioning. Realization of the safe production is the main goal of continuous systems at the open pits. In order to achieve this goal, it is necessary to determine the availability of a continuous system. To determine the availability, data related to the I BTD system of the open pit Drmno Kostolac, more precisely the base with various downtimes over a period of 3 years (2016-2018), was used. This paper presents a case study for determining the availability of a continuous system at the coal open pit Drmno using an analytical model. The model can be applied to determine the availability of continuous systems at the open pit in the function of design, planning and implementation of production and maintenance systems and, as such, is applicable in the other industrial areas as well.